Hypertension and related diseases in the era of COVID-19: a report from the Japanese Society of Hypertension Task Force on COVID-19 - Shibata, Shigeru; Arima, Hisatomi; Asayama, Kei; Hoshide, Satoshi; Ichihara, Atsuhiro; Ishimitsu, Toshihiko; Kario, Kazuomi; Kishi, Takuya; Mogi, Masaki; Nishiyama, Akira; Ohishi, Mitsuru; Ohkubo, Takayoshi; et al. (Hypertension research, 2020)
Coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected more than seven million people worldwide, contributing to 0.4 million deaths as of June 2020. The fact that the virus uses angiotensin-converting enzyme (ACE)-2 as the cell entry receptor and that hypertension as well as cardiovascular disorders frequently coexist with COVID-19 have generated considerable discussion on the management of patients with hypertension. In addition, the COVID-19 pandemic necessitates the development of and adaptation to a "New Normal" lifestyle, which will have a profound impact not only on communicable diseases but also on noncommunicable diseases, including hypertension. Summarizing what is known and what requires further investigation in this field may help to address the challenges we face. In the present review, we critically evaluate the existing evidence for the epidemiological association between COVID-19 and hypertension. We also summarize the current knowledge regarding the pathophysiology of SARS-CoV-2 infection with an emphasis on ACE2, the cardiovascular system, and the kidney. Finally, we review evidence on the use of antihypertensive medication, namely, ACE inhibitors and angiotensin receptor blockers, in patients with COVID-19.